2018
DOI: 10.1007/s00170-018-2352-8
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of a biocompatible titanium alloy during orthogonal micro-cutting employing green machining techniques

Abstract: The sustainability of a process is the objective of modern industries aiming to reduce waste in production, since consumers require high quality and efficiency with fair price. Thus, a good understanding of the process should be its starting point. The manufacture of dental implants is an example in which waste reduction is important for the reduction of prices due to the demand for great quality and accuracy. This study observed the behaviour of sustainable micro-cutting applied to the Ti-6Al-7Nb titanium all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 48 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Lauro et al 5 conducted a very thorough study in Ti6Al7Nb dry micro turning and assessed several responses that characterize the machinability, including machining forces, cutting temperature, chip compression ratio, specific cutting energy and friction coefficient at the rake face. The same authors 6 performed similar tests with minimum quantity lubrication (MQL) and observed worse surface roughness for MQL conditions due to higher chip adherence ( R a <0.2 μm for dry, and R a <0.3 μm for MQL). Nonetheless, MQL improved the burr formation by avoiding the growth of a build-up edge.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, Lauro et al 5 conducted a very thorough study in Ti6Al7Nb dry micro turning and assessed several responses that characterize the machinability, including machining forces, cutting temperature, chip compression ratio, specific cutting energy and friction coefficient at the rake face. The same authors 6 performed similar tests with minimum quantity lubrication (MQL) and observed worse surface roughness for MQL conditions due to higher chip adherence ( R a <0.2 μm for dry, and R a <0.3 μm for MQL). Nonetheless, MQL improved the burr formation by avoiding the growth of a build-up edge.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, due to the use of positive chip breaker higher cutting speeds and DoC can be used so that productivity can be improved. Lauro and Brandao [17] reported reduced machining performance using minimum quality lubrication (MQL). Dry machining exhibited better results for cutting forces, surface roughness and burr formation compared to MQL.…”
Section: Introductionmentioning
confidence: 99%